ATP-Dependent Chromatin Remodeler CSB Couples DNA Repair Pathways to Transcription with Implications for Cockayne Syndrome and Cancer Therapy - Rabeya Bilkis; Robert J. Lake; Hua-Ying Fan (Cells)
Efficient DNA lesion repair is crucial for cell survival, especially within actively transcribed DNA regions that contain essential genetic information. Additionally, DNA breaks in regions of active transcription are prone to generating insertions and deletions, which are hallmark features of cancer genomes. Cockayne syndrome protein B (CSB) is the sole ATP-dependent chromatin remodeler that is essential for coupling DNA repair pathways with transcription, leading to more efficient DNA repair in regions of active transcription. CSB is best known for its essential function in transcription-coupled nucleotide excision repair (TC-NER), a process that rapidly removes helix-distorting DNA lesions that stall RNA polymerase II, such as those created by chemotherapeutic platinum compounds and UV irradiation. In addition to NER, CSB has also been reported to couple homologous recombination to transcription. Most recently, CSB has also been shown to couple single-strand DNA break repair to transcription. In this review, we will discuss the overlapping and distinct mechanisms by which CSB couples these different DNA repair pathways to transcription. We will also discuss how these CSB functions may account for Cockayne syndrome and the emerging roles of CSB as an innovative target for cancer therapy.